THE RELATIONSHIP OF HYPERTENSIVE HEART DISEASE (HHD) TO THE INCIDENCE OF CORONARY HEART DISEASE IN 2023 AT IBNU SINA HOSPITAL, MAKASSAR CITY - Nurkhaliza, A.; Wisudawan, Wisudawan; Basri, Rezky Pratiwi L.; Kanang, Indah Lestari Dg; Tahir, Akina Mauldhany (HEARTY, 2025)
Background: Hypertensive heart disease (HHD) is a long-term consequence of chronic high blood pressure. Persistent high blood pressure is a major risk factor for the development of heart diseases such as atherosclerotic disease, heart failure, atrial fibrillation, and coronary heart disease. Objective: To determine the relationship of Hypertensive Heart Disease (HHD) to the incidence of Coronary Heart Disease (CHD) in 2023 at Ibnu Sina Hospital Makassar City. Methods: Analytic observational research with cross sectional method. Results: HHD patients who suffered from CHD were 29 people (38.7%), while HHD patients who did not suffer from CHD were 46 people (61.3%) p value of 0.735 with chi-square test. Conclusion: There is no significant relationship between Hypertensive Heart Disease (HHD) and the incidence of Coronary Heart Disease.